From Scrolling To Strolling: Synergizing Tourism Influencers and AI Adoption in Gen Z’s Decision To Visit Marine Destination - Zulfa Indriyani; Mohamad Rifqy Roosdhani; Sisno Riyoko (JURNAL PELITA MANAJEMEN, 2026)
The rapid integration of digital technology has transformed how Generation Z plans travel, creating a dichotomy between human-centric social validation and machine-driven utility. However, previous studies have largely examined tourism influencers and AI usage separately, despite Gen Z marine tourism decisions being increasingly shaped by the interaction of social influence, digital engagement, and AI-assisted planning. This integration is particularly important in marine tourism contexts, where experiential decision-making is highly influenced by both social validation and digital assistance technologies.This study investigates the transformation mechanism of digital stimuli into behavioral intentions by examining the synergistic roles of Tourism Influencers and Artificial Intelligence (AI) Usage in predicting Visit Decisions to marine tourism destinations in Jepara, Indonesia. Utilizing the Stimulus-Organism-Response (S-O-R) framework, this quantitative research employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data from 145 Gen Z respondents selected through purposive sampling. The results indicate that the proposed model demonstrates substantial predictive power. Empirical findings reveal that Tourism Influencers significantly drive the quality of Tourism Content and Digital Engagement. Crucially, this study identifies Digital Engagement as the most dominant mediator, outperforming Tourism Content in converting influencer exposure into visit decisions. Conversely, although AI Usage has a significant yet relatively weak direct effect on visit decisions, AI failed to serve as a significant mediator in the context of influencer marketing. These findings conclude that for Gen Z, AI currently functions as a complementary utility tool, whereas active digital engagement remains the primary psychological bridge for behavioral conversion. Destination managers are advised to shift strategies from passive content exposure to fostering interactive digital participation.